Activation of Factor X - Lechner, K; Deutsch, E (Thrombosis and Haemostasis, 1965)
1. Methods have been developed for the preparation of factor VII free of prothrombin and factor X, and of factor X with only a very low contamination with factor VII.2. Factors VII and X could be found with one stage methods in purified prothrombin prepared according to Seegers.3. Purified prothrombin was chromatographed on DE AE-cellulose. Two active fractions could be eluted, the first with the characteristics of Seegers’ DE AE-Prothrombin, the second with the characteristics of factor X.4. It was confirmed that DE AE-Prothrombin does not activate to thrombin in 25% citrate, and does not generate autoprothrombin C.5. The combination of both clotting active fractions coming from the DEAE-column restores the properties of non-chromatographed prothrombin.6. DE AE-cellulose chromatography of prothrombin does not induce a molecular change of prothrombin, but separates factor X from prothrombin.7. Factor X can be activated with tissue thromboplastin-factor VII or with high concentrated neutral salt solutions to a substance with the biological characteristics of autoprothrombin C.8. TAMe activity is generated in factor X preparations after incubation with tissue thromboplastin and calcium.9. Factor VII cannot be transformed into autoprothrombin C under the conditions tested.10. Factor VII is necessary for the activation of factor X with tissue thromboplastin but not with RVV.11. The amount of factor X available determines the amount of autoprothrombin C formed, whereas thromboplastin and factor VII influence the rate of the reaction.12. The final conclusion is that activated factor X is similar to or identical with autoprothrombin C.